Challenges in Implementing and Sustaining Community College Organizational Change for Student Success - Jennifer Miller; Christine Harrington (Journal of Postsecondary Student Success, 2023)
Community colleges are challenged with creating and sustaining student success organizational change. Institutional-level student success reform efforts are needed to combat the unacceptably low student completion rates, but colleges often struggle to initiate and maintain organizational reforms. After many years of reform efforts, researchers have provided theories for whole college organizational change, in particular guided pathways, that shows great promise in helping community colleges realize student success and completion gains while targeting and reducing racial equity gaps. A literature review focused on determining the internal reasons why institutions struggle to create and sustain organizational change was conducted. Contextual challenges, awareness and motivation, and change management process challenges within the institutions were several of the key causes identified. Within contextual challenges, organizational structures including college policies, practices, and governance, as well as leadership and funding challenges were cited as barriers to organizational change for student success. A lack of awareness of the need for or how change by faculty, staff, and administrators, along with a lack of motivation or resistance to the change can also create significant roadblocks for colleges. Change management process challenges within the institution including a lack of professional development for leaders in change management strategies was also cited as a significant challenge to developing and sustaining an effective organizational change effort. Knowing these challenges can lead to informed approaches that college leaders, faculty, and staff take to implement, hopefully helping institutions sustain change reform at scale over the long-term and ultimately benefit the overall goal of increased student success and completion.